Gender and Community Development Implications in Thailand - Khunthongjan, Supawadee (Thammasat Review, 2026)
This study employed a mixed-methods research design that integrated quantitative and qualitative data collection in order to capture, in a comprehensive manner, the dynamic relationship between gender roles and the developmental trajectory of local communities. The quantitative component was conducted through a questionnaire constructed on the basis of conceptual frameworks concerning institutional roles, gender, and development, with respondents drawn from residents of Naton Subdistrict, Thailand who had participated in local development activities or projects. The reliability of the research instrument was examined using Cronbach’s alpha coefficients, together with tests for multicollinearity to confirm the stability of the independent variables in the quantitative model. The qualitative component consisted of in-depth interviews with key informants, including local council members, community leaders, and women who play significant roles in community development initiatives. The qualitative informants and the quantitative respondents were not drawn from an identical pool, a design intended to enhance the diversity of perspectives and reduce potential data bias. Qualitative analysis drew on inductive thematic extraction, institutional interpretation, and triangulation with the quantitative results so as to generate findings that are both analytically rich and coherently linked.